Promoting a Contextualized Learning Experience Through the Implementation of PBA and the Use of Authentic Materials in Fourth-graders at Juan María Céspedes (2021)
ABSTRACT: This action research aimed at defining to what extent the implementation of project based approach using authentic materials promotes a contextualized learning experience in primary school students. The participants were 18 students from group 4-4 at Educational Institution Juan María Céspedes. Actions consisted in the creation of a project in which students presented some facts about a country. Authentic materials were used as input in all stages of the project in order to have a more contextualized perspective of the target language. Data collection instruments included a teacher journal, students artifacts, a student survey, and an interview with the cooperating teacher. Findings suggested that CTL had a positive impact on students, authentic materials helped the enhancement of reflective thinking and PBL promoted the awareness of students’ own learning processes.